Sociology of the Environment - Marcus, Benny (TRAILS: Teaching Resources and Innovations Library for Sociology, 2013)
This course will introduce you to the sociology of the environment, the study of the interrelationships of human social systems and ecosystems, with a primary focus on their social aspects. These interrelationships occur on various scales, from the local to the global, and are profound and complex. Humans are part of the natural environment but have long thought of themselves as separate from and opposed to it. The well being of social systems depend on ecosystems, but social systems are now the major influence on their degradation. The core issues of environmental sociology concern the effects of social systems on the environment and how social systems can be rearranged to ensure environmental justice and sustainability. We will examine these issues by first surveying environmental sociology’s primary perspectives then analyzing more closely some of the most significant of them.